Pre-Sowing Static Magnetic Field Treatment of Vegetable Seeds and Its Effect on Germination and Young Seedlings Development - Athanasios Koukounaras; Achilles Boursianis; Stefanos Kostas; Argyris Theopoulos; Filippos Bantis; Theodoros Samaras (Seeds, 2023)
The pre-sowing treatment of seeds with an α static magnetic field has been reported in the literature as a means of enhancing plant development. In this work, we have designed, characterized, and constructed a setup for exposing small vegetable seeds to a static magnetic field. In a series of experiments, we have treated the seeds of vegetables that are important for the Mediterranean diet, i.e., tomato, lettuce, and salad rocket. The results show that tomato seedlings significantly benefit from a pre-sowing treatment with a magnetic flux density of 45 mT, for both an exposure time of 60 and 90 min compared to control, while the time of treatment that leads to improved growth is 90 min. In order to improve the growth of salad rocket seedlings the magnetic field had to be 150 mT, whereas the results for lettuce seeds were a bit inconsistent, i.e., it is not clear whether a lower (45 mT) or a higher (300 mT) magnetic flux density should be applied.